Increasingly Geopolitical? The EU’s Approach Towards the Post-Soviet Space - Nitoiu, Cristian (Journal of Regional Security, 2018)
Throughout the past decade the policy of the European Union (EU) towards its eastern neighbours has avoided focusing on security issues. However, the Ukraine crisis had had a deep impact on the EU’s foreign policy and its approach towards post-Soviet space. It has highlighted that the EU’s eastern neighbourhood is characterised by intense geopolitical competition with Russia. The crisis also underscored the weakness of the EU’s low politics approach towards the post-Soviet space and Russia. On the other hand, Russia’s actions in Ukraine have made the member states more willing to act together and recognise Russia as a security threat. In this context, the article argues that while the EU has not always viewed its relations with Russia and the post-Soviet space in traditional geopolitical terms, the shape of the regional geopolitical structure has always influenced its policy towards the region. Moreover, the article shows how the EU has gradually embraced geopolitical competition for influence in the post-Soviet space with Russia and even confrontation with Moscow.